Working Memory in Aphasia: The Role of Temporal Information Processing - Choinski, Mateusz; Szelag, Elzbieta; Wolak, Tomasz; Szymaszek, Aneta (Frontiers in Human Neuroscience, 2020)
Aphasia is an acquired impairment of language functions resulting from a brain lesion. It is usually accompanied by deficits in non-linguistic cognitive processes. This study aimed to investigate in patients with aphasia the complex interrelationships between selected cognitive functions: auditory speech comprehension, working memory (WM), and temporal information processing (TIP) in the millisecond time range. Thirty right-handed subjects (20 males) aged from 27 to 82 years suffering from post-stroke aphasia participated in the study. Verbal working memory (VWM) and spatial working memory (SWM) were assessed with: (1) a receptive verbal test and (2) the Corsi Block-Tapping Test, respectively. Both these WM tests used the forward tasks (mainly engaging maintenance processes, i.e., storing, monitoring, and matching information) and backward tasks (engaging both maintenance and manipulation processes, i.e., reordering and updating information). Auditory comprehension was assessed by receptive language tests, and TIP efficiency was assessed by auditory perception of temporal order in the millisecond time range. We observed better performance of forward WM tasks than backward ones, independently of the type of material used. Furthermore, the severity of auditory comprehension impairment correlated with the efficiency on both forward and backward VWM tasks and the backward SWM task. Further analysis revealed that TIP plays a crucial role only in the latter task. These results indicate the divergent pattern of interactions between WM and TIP depending on the type of WM tasks. Level of verbal competency appeared to play an important role in both VWM tasks, whereas TIP (which is associated with manipulation processes) appeared to be important for SWM, but only on the backward task.